Analysis of Locutionary Speech Acts in Fauzan Al-Rasyid's Twitter Account Posts Regarding Language - Nabila Zata Yumni; Fajrinna Kusuma Handayani; Anggita Sonyaruri; Imtiyaza Nihlah Hadana; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Nurnaningsih Nurnaningsih (International Journal of Educational Technology and Society, 2024)
English translation. The rapid advancement of technology encourages more diverse interactions in languages, one of which is followed by the emergence of various social media. The following research aims to discuss linguistic interactions regarding locutionary speech acts in Pragmatics. Unlike previous studies, this data was taken from utterances that discussed Indonesian language material uploaded by a Twitter user. Starting from discussing UTBK questions, PBM, language issues, to updates regarding the EYD (Edition V) which is implemented in Indonesia. This study aims to determine the intent and form of locutionary speech acts in Fauzan Al-Rasyid's Twitter account uploads regarding this linguistic material. This article applies a research method with a pragmatic and descriptive qualitative approach that uses techniques of reading, observing, and documenting the data to be collected. Documentation techniques are used to collect data, reduce data, display data, and verify the data taken so that all data is neatly arranged and properly recorded. The results of this study, the researcher found 15 speech data where all the data were in the form of locutionary speech acts. The 15 data have the intention of conveying information and giving confirmation from speakers to speech partners related to language. Then, in presenting the data, the writer uses formal and informal presentation. This research is expected to provide an understanding of locutionary speech acts and can be used as a basis and reference or reference by other researchers who wish to conduct similar research in order to improve their problem-solving skills or as an effort to improve their analytical skills .